O-band multi-wavelength fiber laser - Ahmad, Harith; Zulkifli, Mohd Zamani; A, A, Latif; Harun, Sulaiman Wadi (World Scientific, 2010)
In this paper, we demonstrated a novel multi-wavelength fiber laser system operating in the O-band (1310 nm) region. The proposed O-band multi-wavelength fiber laser uses a 1 × 24 Arrayed Waveguide Grating to generate eight output channels simultaneously with a span width of 14.05 nm. In addition to this, the tunability of a single wavelength output is also demonstrated using a 1 × 16 AWG together with an optical channel selector. A Semiconductor Optical Amplifier (SOA) operating at 1310 nm is used as the gain medium to provide the spontaneous and stimulated emissions required for the laser operation. The fiber laser has a tuning range of 1301.26 nm to 1311.18 nm with 9.92 nm span and channel spacing of 0.7 nm. © 2010 World Scientific Publishing Company.